PENGARUH LINGKUNGAN KERJA, PENGHARGAAN FINANSIAL, MOTIVASI DIRI, DAN KECERDASAN ADVERSITY TERHADAP MINAT BERKARIR AKUNTAN PUBLIK - Bhaskara, Agus Yoga; Latrini, Made Yenni (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.01.TAHUN.2024, 2024)
Economic development in an area is influenced by several things, one of which is the profession as a public accountant to support the economic development of a country to be effective and efficient in the aspect of transparency. This profession is proven to have a role in supporting economic development in a country, in order to increase effectiveness and efficiency related to the strength of transparency. However, the number of these professions is still low. This study focuses on finding empirical evidence of the effect of the variables used on student interest in a career as a public accountant. The probability sampling technique was chosen in random sampling. The sample used in this research was 72 respondents. The findings show that the work environment, financial rewards, self-motivation, and adversity intelligence have a positive effect on students' interest in a career in public accounting.